Bundling information goods and access – simulating competition - Bronwyn E. Howell; Petrus H. Potgieter (International Telecommunications Society (ITS), 2018)
We discuss the effect of pricing strategies by two firms on the total firm revenue, consumer and total welfare using simulation and numerical analysis. We consider pricing decisions for mixed bundling and where each firm offers two closely related products as well as a bundle. Bundling is a key feature for information goods (Bakos & Brynjolfsson, 1999; Shapiro & Varian, 1999) and we might assume that the market has two differentiated content products (each of which is a bundle of channels, for example, or a bundle of content titles to which access is sold). In many markets, this would be a basic entertainment product and then a sports product or a premium bundle with recent films etc. We can also consider this to be an access and a content product, to consider the issues around merger of content and access firms. In the model for this paper, we introduce a principle of bounded rationality by limiting the ability of the firms to determine revenue-maximising pricing strategies. That means that the firms are able to reduce their effort to find a revenue optimum and will in general find a relatively good solution only but not necessarily an optimum one. Considering the effects of this approach might be useful for both regulators and firms. We also assume that the firms collude to maximise their joint revenue, which we regard as a realistic supposition in a duopoly market. The model can be extended to cover the case where one firm offers/bundles more than two products but this is a topic for future research.
Keywords: 330